Sustainability and the real value of care in times of a global pandemic: SDG5 and Covid-19 - Flora Ijjas (Discover Sustainability, 2021)
Abstract The pandemic Covid-19 has been affecting the global population, causing profound social and economic problems. The aim of this paper is to analyse the health crises from an ecological economic and a gender equality perspective in order to see how the pandemic is affecting Sustainable Development Goal 5 (gender equality) and particularly Target 5.2 which is about eliminating domestic violence and 5.4 which is about the valuation of unpaid care and domestic work. Secondary data, facts and thoughts from scientific papers and other documents are being reviewed to understand our socio-economic systems’ effects on the reproduction of nature and on social reproduction. Results show, that capitalist systems exploit regenerative and reproductive workers of the demonetized economy, such as nature, unpaid caregivers, peasants, and indigenous gatherers. These exploitative systems also have contributed to the rise of the new pandemic Covid-19 by destroying natural habitats. The virus might have some short-term positive effects on the environment, but the backbone of society’s response is unpaid care work, therefore women are being exploited even more. Conclusions are, that patriarchal characteristics, such as normalized systematic domination and oppression of women (and other regenerative and reproductive workers) are on the long run a burden for the SDGs.